Application of airbone geophysical and reomote sensing data to the interpretation of geologic setting in Nan-Uttaradit area, Northern Thailand - Rawiwan Rittisit (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2011